Interactive E-Texts and Students: A Scoping Review - Spencer, Rebecca; Comeau, Emilie; Matchett, Brittany; Biderman, Maya; Joy, Phillip; Doria, Nicole; Numer, Matthew (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
The purpose of this article is to explore the scope of available evidence regarding the use of interactive e-texts and their relationship to student learning experiences in post-secondary education. Following the framework of Arksey and O’Malley, this scoping review identified and reported on 33 articles. Study characteristics are presented alongside four themes that were found across the included articles: (1) the effect of interactive e-texts on student learning experiences; (2) the relationship between interactive e-texts and academic performance; (3) factors influencing student adoption and experience of interactive e-texts; and (4) roles, responsibilities, and recommendations. While the adoption of interactive e-texts is becoming increasingly common in post-secondary education, their effect on student learning experiences remains complex. This review emphasizes the importance of user-friendliness, affordability, accessibility, portability, and the role of educators. Using interactive e-texts shows promise, though future research should explore how barriers might be minimized and benefits might be maximized to have the strongest impact on student learning experiences. Keywords: interactive e-text, student experience, scoping review, post-secondary education